Ixodes ricinus ticks (Acari: Ixodidae): vectors for Lyme disease spirochetes in Romania - Coipan, Elena Claudia; Vladimirescu, Alexandru Filip (Experimental & applied acarology, 2011)
In this study 1,868 questing Ixodes ricinus ticks (nymphs and adults), collected in six sites from three counties—Giurgiu, Sibiu, and Tulcea—in Romania, were examined by polymerase chain reaction (PCR) followed by reverse line blot (RLB) for detection of Borrelia burgdorferi sensu lato presence. The bacteria were found in 18% of the investigated ticks. The prevalence of infection did not differ significantly between nymphs (19.1%) and adults (15.4%). Three B . burgdorferi s.l. genospecies were detected: B. afzelii (61.1%), B . garinii (31.2%), and B . valaisiana (7.7%). No mixed infections were detected. The highest infection prevalence in nymphs was detected at Cristian (Sibiu County)—22.0%, whereas in adults it was at Comana (Giurgiu County)—19.8%. This preliminary study provides evidence that Lyme disease spirochetes are present in various regions of Romania, and at a relatively high prevalence in their vectors, thus posing a risk of infection to human subjects in the areas infested by ticks.